The Influence of Authoritarian Parenting on Students’ Morality and Ethics in Schools: Systematic Literature Riview - Muhamad Desta Dwi Putra; Winda Alawiah; Puspa Surya Utami; Cindy Marisa (CERDAS AKADEMIKA NUSANTARA, 2025)
This research aims to analyze the influence of parents' authoritarian parenting styles on students' moral and ethical development at school through a Systematic Literature Review (SLR) approach. Data was collected from Google Scholar with the keywords parenting style, authoritarian, morals, ethics, students so that 5,000 articles were obtained. The 2021–2025 inclusion selection produced 2,790 articles, then focused on additional keywords school and quantity until 1,580 articles remained. After final filtering based on the relevance of variables and methods, 23 articles were obtained which were analyzed using the PRISMA method. The results of the analysis show that authoritarian parenting has a negative effect on students' morals and ethics. Children are more likely to obey because of fear, not moral awareness, so they are less able to internalize the values ​​of honesty, discipline and responsibility. These findings confirm that authoritarian parenting styles hinder the formation of positive morals and ethics in schools.